THE AMBIGUITY OF ENGLISH ADVERTISEMENT - Dian Anik Cahyani; Aang Fatikhul Islam (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2017)
This is a qualitative research on applied linguistic which is conducted to find applied semantic theory about ambiguity, a condition where an utterance has two or more interpretations. The writers uses Kreidler’s theory which classifies ambiguities into three kinds; lexical, referential, and syntactic which is devided into two types; surface structure and deep structure. The discussion includes kinds of ambiguity that are found and their interpretations. The data sources is English advertisement and the data is English advertisement utterances in banners, posters, and billboards. The writers collects the datas by taking in a picture, sellecting, and presenting. The next is analysis and conclusion. There are 33 datas that are found, they are twelve banners, eleven posters, and ten billboards. From banners, there are three lexical, no referential, six surface structure, and three deep structure ambiguities. From posters, there is no lexical, one referential, four surface structure, and six deep structure ambiguities. From billboards, there are two lexical, two referential, four surface structure, and two deep structure ambiguities. Generally, the ambiguities are dominated by surface and deep structure ambiguity.